Design of Multilayer Dielectric Cover to Enhance Gain and Efficiency of Slot Arrays - Giorgio Montisci; Zusheng Jin; Mingchao Li; Hu Yang; Giovanni Andrea Casula; Giuseppe Mazzarella; Alessandro Fanti (International Journal of Antennas and Propagation)
An effective design procedure, based on the Elliot synthesis method, is proposed to investigate the properties of waveguide slot arrays with multilayer dielectric cover. Then, the features of the designed arrays are analyzed by means of a FEM commercial software, namely, Ansys HFSS 13. We show how a proper choice of the dielectric cover configuration allows increasing the array gain and aperture efficiency, while taking advantage of the properties of the radome structure, in terms of insulation, protection, and pressurization of the radiating waveguides. Therefore, a significant outcome of the optimal choice of the multilayer dielectric cover is the reduction of the number of slots with respect to an array radiating into free space with the same gain and efficiency, with a consequent reduction of the production cost.